2021
DOI: 10.3390/metabo11120866
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced β-carotene and Biomass Production by Induced Mixotrophy in Dunaliella salina across a Combined Strategy of Glycerol, Salinity, and Light

Abstract: Current mixotrophic culture systems for Dunaliella salina have technical limitations to achieve high growth and productivity. The purpose of this study was to optimize the mixotrophic conditions imposed by glycerol, light, and salinity that lead to the highest biomass and β-carotene yields in D. salina. The combination of 12.5 mM glycerol, 3.0 M salinity, and 50 μmol photons m−2 s−1 light intensity enabled significant assimilation of glycerol by D. salina and consequently enhanced growth (2.1 × 106 cell mL−1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Thus, in order to increase the economic efficiency of the heterotrophic bio-oil production technology using microalgae, other, cheaper sources of carbon should be used. One of the proposed solutions is waste technical glycerin, which allows a high final concentration of microalgae biomass and desired bioproducts to be obtained [ 32 , 33 ]. Rattanapoltee et al (2021) confirmed the marginal influence of impurities in raw technical glycerin, e.g., soap, methanol, on the final concentration of biomass and the final content of valuable fermentation products such as DHA [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in order to increase the economic efficiency of the heterotrophic bio-oil production technology using microalgae, other, cheaper sources of carbon should be used. One of the proposed solutions is waste technical glycerin, which allows a high final concentration of microalgae biomass and desired bioproducts to be obtained [ 32 , 33 ]. Rattanapoltee et al (2021) confirmed the marginal influence of impurities in raw technical glycerin, e.g., soap, methanol, on the final concentration of biomass and the final content of valuable fermentation products such as DHA [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The transcriptome analysis conducted by Li et al (2020) also showed that red light is most suiTablele for algal growth, with stronger expression of growth-control genes compared to blue light. In contrast, cellular carotenoid content as well as the expression of reactive oxygen species (ROS) synthase genes were enhanced under blue-spectrum illumination [13].…”
Section: Discussionmentioning
confidence: 99%
“…With regards to culture medium condition, many studies have been conducted in an effort to find out the optimal condition of culture that stimulates the highest production of biomass and β-carotene, that mostly focused on nutritional factors (i.e., composition and content) and major environmental factors (i.e., salinity, temperature, pH of the culture medium and light intensity) [10][11][12]. Capa-Robles et al (2021) reported that a combination of 12.5 mM glycerol, 3.0 M salinity, and 50 μmol photons m −2 s −1 light intensity resulted in the best growth of 2.1 × 10 6 cell mL ) of the Mexican strain, D. salina BC02 [13]. In the study of Mohammadi et al (2023), the optimal condition for the growth of D. salina was at 3 molars salinity, pH higher than 7, nitrate concentration of 0.25 g/L, light intensity of 5000 lux, and temperature of 25 degrees Celsius, whereas the optimum β-carotene production occurred at a similar condition of these parameters but in a temperature of 30 degrees Celsius [14].…”
Section: Introductionmentioning
confidence: 99%
“…1). The reason might be that the osmotic pressure modification in the culture medium along with low photon flux density stressed the microalgae, triggering lipid production and limiting biomass production (Capa-Robles et al 2021).…”
Section: Total Lipidsmentioning
confidence: 99%